Analisis Kemampuan Belajar Siswa dengan Penerapan Inkuiri pada Materi Sistem Ekskresi - Halimatussa'diyah, enni; Hartono, Adi; Wahyu , Eka; Yanti , Depi; Marshelli, Melvi (Comit: Communication, Information and Technology Journal, 2024)
Education plays an important role in improving the quality of human resources to create general welfare and educate the nation by forming a superior, quality, and competitive generation. This study aims to describe student learning outcomes in the biology learning process by using an inquiry learning model on the material of the human excretory system. This study uses the method of library research (library research), where the study is based on expert opinions about business ethics and its role in the company. In addition, this journal also uses the comparative study research method which aims to compare two or more variables to get answers or facts whether the comparison or not of the object under study. Based on the results of the discussion, it can be concluded that the inquiry learning model can improve students' critical thinking skills in biology subjects on excretion material. The use of inquiry learning models makes students able to understand the material well, plays an active role during the learning process, and improves students' critical thinking skills. Keywords: Inquiry, Excretion, Students